Development of Integrated Science E-Learning Modules Based on Bangka Belitung Ethnoscience Subjects in Junior High Schools - Firanita Fitriyah; Siti Sriyati; Rika Rafikah Agustin (FKIP - Universitas Riau, 2026)
This study aims to integrate science learning with local wisdom in Bangka Belitung into teaching materials in the form of integrated science E-Modules based on ethnoscience to improve science process skills. This development follows the ADDIE development process, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The analysis stage focuses on the needs that are used as information for development. The design stage focuses on developing the content and format of the E- Module in accordance with the concept map and storyboard to produce an initial product. In the development stage, the initial product was validated by experts consisting of expert lecturers and teachers as science learning practitioners. The validation results showed that the developed E-Module was very suitable for use because it received a very valid category with a score of 85.80% from content validation and 86.99% from construct validation. In the implementation stage, the average response of students to the use of E- Modules in learning was 91.84%. Thus, the developed E- Module is considered feasible, practical, and effective in science learning.